L-/M-cone opponency in visual evoked potentials of human cortex - Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; Gomes Martins, Cristiane Maria; Oliveria Bonci, Daniela Maria; Hauzman, Einat; Aher, Avinash; Tsai, Tina I.; Kremers, Jan; Ventura, Dora Fix (Journal of Vision, 2017)
L and M cones send their signals to the cortex using two chromatic (parvocellular and blue-yellow koniocellular) and one luminance (magnocellular) pathways. These pathways contain ON and OFF subpathways that respond to excitation increments and decrements respectively. Here, we report on visually evoked potentials (VEP) recordings that reflect L- and M-cone driven increment (LI and MI) and decrement (LD and MD) activity. VEP recordings were performed on 12 trichromats and four dichromats (two protanopes and two deuteranopes). We found that the responses to LI strongly resembled those to MD, and that LD and MI responses were very similar. Moreover, the lack of a photoreceptor type (L or M) in the dichromats led to a dominance of the ON pathway of the remaining photoreceptor type. These results provide electrophysiological evidence that antagonistic L/M signal processing, already present in the retina and the lateral geniculate nucleus (LGN), is also observed at the visual cortex. These data are in agreement with results from human psychophysics where MI stimuli lead to a perceived brightness decrease whereas LI stimuli resulted in perceived brightness increases. VEP recording is a noninvasive tool that can be easily and painlessly applied. We propose that the technique may provide information in the diagnosis of color vision deficiencies.
EVALuna2:21340